2013
DOI: 10.1074/jbc.m113.496679
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Nuclear Ribonucleoprotein (HnRNP) K Genome-wide Binding Survey Reveals Its Role in Regulating 3′-End RNA Processing and Transcription Termination at the Early Growth Response 1 (EGR1) Gene through XRN2 Exonuclease*

Abstract: Background: Mapping heterogeneous nuclear ribonucleoprotein (hnRNPK) genome-wide binding could better define its role in transcription. Results: ChIP-Seq revealed hnRNPK accumulation at 3Ј-ends of immediate early genes. HnRNPK knockdown altered degradation of RNA downstream of poly(A) at EGR1 by decreased binding of XRN2 exonuclease. Conclusion: HnRNPK facilitates XRN2 recruitment influencing co-transcriptional 3Ј-end mRNA processing. Significance: A novel hnRNPK-dependent process has been identified in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…Under these conditions, we detected increased readthrough transcripts of MYC and FRAT2 (Fig. 6F), consistent with previous reports (West et al 2004;Mikula et al 2013). We also saw increased transcription past normal CCNB1 termination signals by conventional PCR-with a forward primer upstream of the PAS and reverse primers at increasing distances downstream-after Xrn2 depletion or CDK inhibition (Supplemental Fig.…”
Section: Cdks and Xrn2 Phosphorylation Promote Transcription Terminationsupporting
confidence: 80%
“…Under these conditions, we detected increased readthrough transcripts of MYC and FRAT2 (Fig. 6F), consistent with previous reports (West et al 2004;Mikula et al 2013). We also saw increased transcription past normal CCNB1 termination signals by conventional PCR-with a forward primer upstream of the PAS and reverse primers at increasing distances downstream-after Xrn2 depletion or CDK inhibition (Supplemental Fig.…”
Section: Cdks and Xrn2 Phosphorylation Promote Transcription Terminationsupporting
confidence: 80%
“…In our study, we observed that C/EBPα and β were significantly deregulated in tissues from Hnrnpk +/− mice. While recent ChIP-Seq studies in cell lines suggest hnRNP K may directly modulate C/EBPβ expression by specifically interacting with its promoter (Mikula et al, 2013), less is known regarding how hnRNP K regulates C/EBPα levels. Examination of the potential interaction between hnRNP K and the C/EBPα and C/EBPβ genes revealed that hnRNP K directly interacts with both genes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, other studies have shown that hnRNP K represses C/EBPβ-mediated differentiation in the liver and that it regulates the expression of genes required for hematopoietic maturation (Miau et al, 1998; Ostareck et al, 1997). Together, these studies suggest hnRNP K plays a critical role in proliferation and differentiation and that deregulation of hnRNP K expression may promote tumorigenesis (Liu and Szaro, 2011; Mikula et al, 2013; van Domselaar et al, 2012; Wang et al, 2011). …”
Section: Introductionmentioning
confidence: 91%
“…For example, SRSF2 regulates transcriptional elongation in a sequence-specific manner via the 7SK complex that governs RNA polymerase II pause release 124 . Similarly, hnRNP A1, hnRNP A2 and hnRNP K are linked to cancer, and hnRNP A1 and A2 have reported roles in transcription elongation whereas hnRNP K is linked to transcription termination 125,126 . Many splicing factors co-transcriptionally associate with the C-terminal domain of RNA polymerase II, thereby coupling transcription, splicing, cleavage and polyadenylation (reviewed in 127 ).…”
Section: Connections To Other Cellular Processesmentioning
confidence: 99%